(untitled) (Scientific journal of the Fergana State University, 2023)
The article highlights a linguo-analysis of the landscape of linguistic world and a general interpretation of the concept of "world landscape". Moreover, the compatibility of LLM in different languages, its penetration into Uzbek linguistics, linguistic relativity, the impact of linguoculturology on LLM and several functions of the concept of LLM are discussed.